STRATEGY FOR IMPLEMENTATION OF INNOVATIVE SERVICES IN HOTEL CATERING ENTERPRISES OF KHARKIV REGION - Свідло, Карина; Мамченко, Людмила; Загоруйко, Діана; Попович, Таміла (SWorldJournal, 2023)
The article discusses the management strategy of catering enterprises using the example of the Ryleev mini-hotel (Kharkov). Examples of different-level innovation cycles are provided for the main types of enterprises that provide catering services in the